Novel homoleptic, dimeric zinc(II) phthalocyanines as gate dielectric for OFET device - Karaoglan, Gulnur Keser; Gumrukcu, Gulsah; Gorduk, Semih; Can, Nursel; Gul, Ahmet (ELSEVIER SCIENCE SA, 2017)
A novel multicomponent system consisting of benzene-1,4-diyldimethanimine bridged dimeric zinc-phthalocyanine groups was synthesized. Firstly, a novel unsymmetrically nitro and 2,4-di-tert-butylphenoxy groups substituted zinc (II) phthalocyanine was synthesized and then nitro group was reduced to amino functional group. All newly synthesized compounds were characterized by UV-Vis, FTIR, H-1-NMR, MALDI-TOF MS and elemental analysis spectral data. The potential of these compounds as gate dielectric were investigated by fabricating bottom gate top contact OFET using poly 3-hexylthiophene-2,5-diyl as active layer. Field effect mobility values of 3.2 x 10(-4) cm(2)/V s was obtained when using ITO-coated glass as gate electrode. It was found that the density of leakage current was about 2 nA/cm(2) at 5 V. The capacitance density of 11.8 nF/cm(2) was achieved at a frequency of 5 Hz with slightly smaller values at higher frequency.
Keywords: Synthesis; Dimeric; Phthalocyanine; Zinc; Dielectric; Ofet; FIELD-EFFECT TRANSISTORS; THIN-FILM TRANSISTORS; METALLOPHTHALOCYANINES; ELECTROCATALYSIS; PORPHYRINS; OXYGEN; Materials Science; Physics; Polymer Science